(untitled) (diségno, 2017)
Digital visualization as the representation of a past that no longer exists is a communicative necessity in which virtual reconstructions have become means and experience of an otherwise intangible time. The case study presented is the expression of a methodology seeking to combine informative and scientific aspects. This method aims to provide an answer to a multidisciplinary approach that characterizes the study of architectural heritage of the past where virtual reconstructions, if scientifically substantiated, can become clear and transmittable documents.